Expression and mutagenesis of bacteriorhodopsin an integral membrane protein - Sidhu, I; Sidhu, Inderjit Kaur (1998)
Although integral membrane proteins represent nearly a quarter of the genes present in both prokaryotes and eukaryotes, progress in this area of research is often hindered due to the nature of their hydrophobic environment. Elucidating the folding pathway of these proteins is essential to understand many membrane mediated biological processes such as signal transduction, ion transport and chemotaxis. The wealth of structural and genetic information on bacteriorhodpsin renders it an ideal model system for the study of membrane proteins. Detailed studies however, necessitate efficient methods for its overexpression and purification. Previous expression systems have reported difficulty in obtaining good yields and simple purification procedures. This thesis investigates a variety of alternative expression and purification systems for the bacterio-opsin gene in Escherichia coli. With sufficient protein, site directed mutagenesis is performed to mutate three proline residues present in the membranous region of bacteriorhodopsin to alanine. The folding kinetics of these mutants is investigated using stopped flow fluorimetry to determine whether proline isomerisation is responsible for a slow step in the folding pathway of bacteriorhodopsin. Comparison of the results with those of the folding kinetics of wild type showed proline isomerisation not to be responsible for the slow step in the pathway. More recent studies have suggested that the slow step may be due to refolding conditions and lateral pressure the lipids impose upon the protein as well as pH. Separate structural studies using mass spectrometry aimed to study the rates of isotopic exchange of amide and side chain protons in bacteriorhodopsin. Low resolution results obtained using matrix assisted laser desorption ionisation mass spectrometry (MALDI-MS) prompted the investigation of electrospray ionisation mass spectrometry (ESI-MS). Techniques for sample preparation were optimised by investigating a variety of solvent systems and initial deuteration experiments performed.